Blood Lead Testing Among Medically Underserved and Socially Vulnerable Children in the United States 2012-2017. Issue 6 (November 2021) - Azofeifa, Alejandro; Sripipatana, Alek
Abstract : Context: Lead poisoning can affect intellectual development, growth, hearing, and other health problems. Children 6 years or younger are particularly susceptible to lead poisoning. Health Resources and Services Administration (HRSA)–funded health centers (HCs) serve lower-income, minority, and vulnerable populations across the United States, who may be at a higher risk for lead exposure. At HCs, blood lead testing is monitored; however, little is known about testing rates and characteristics of children tested by HCs. Objectives: We assessed the prevalence and characteristics of children who received a blood lead test at HCs from 2012 to 2017. Design: We assessed characteristics of children 12 to 60 months of age who had a blood lead test using available self-reported data from HRSA's Health Center Patient Survey (2014-2015). In addition, using HRSA's Uniform Data System, an administrative performance data set, we calculated the annual percentage change of blood lead testing from 2012 to 2017. Results: During 2014-2015, 1.1 million (72.9%; 95% CI, 64.6-81.3) out of the 1.5 million (n = 365 unweighted) eligible children 12 to 60 months of age self-reported receiving a blood lead test at an HRSA-funded HC. There was a significant higher proportion of children with a blood lead test among urban HCs (74.1%; 95% CI, 59.4-88.8) and among those who reported HCs as their usual source of care (99.9%; 95% CI, 99.7-100) ( P ⩽ .05). The total HC population of children younger than 72 months increased from 2 674 500 in 2012 to 2 989 184 in 2017, and we observed a 34.4% increase in blood lead testing at HRSA-funded HCs over the same time period. Conclusions: HCs play an important role in providing access to blood lead testing in underserved communities in the United States. While HRSA-funded HCs have made substantial efforts to screen and educate patients on lead exposure, nonetheless continued screening and education efforts with both health providers at HCs and parents/guardians are warranted to continue to improve blood lead screening rates among high-risk groups.